16.5k views
0 votes
If f(x) = 3x +4, g(x) = 9x + 12, and h(x) = 9x^2 + 24x + 16, then (g-f)(1)=

If f(x) = 3x +4, g(x) = 9x + 12, and h(x) = 9x^2 + 24x + 16, then (g-f)(1)=-example-1
User Eiri
by
6.3k points

1 Answer

4 votes

First, let's calculate the composite function (g-f)(x):


\begin{gathered} (g-f)(x)=g(x)-f(x)\\ \\ =9x+12-(3x+4)\\ \\ =9x+12-3x-4\\ \\ =6x+8 \end{gathered}

Now, let's use x = 1 and calculate the value of the expression:


(g-f)(1)=6\cdot1+8=6+8=14

Therefore the value of (g-f)(1) is equal to 14.

User Jeano
by
6.5k points